A Systematic Review of the Effect of Social Support on Post-Traumatic Stress Disorder in Post-Earthquake Adolescents - Glorya Riana Latuperissa; Wiwi Rumaolat; Inta Susanti; Fathmy Fitriany Soulisa (Jurnal Ners, 2020)
Introduction: Earthquakes can cause mental health disorders in adolescents, one of which is post-traumatic stress disorder (PTSD). The present study aimed to assess the effect of social support on post-traumatic stress disorder in adolescents after an earthquake.Methods: The study was a systematic review with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. Articles were searched for using the Scopus, ScienceDirect, ProQuest, EBSCO and SAGE databases before classifying them into 3 categories: prevalence, risk factors, social support, and post-traumatic stress disorder. The inclusion criteria regarding the literature were documents that were original; where the source was from a journal; where the article was written in English and where the full text was available.  The age of the subjects in the articles was determined to be in the range of 10-20 years old. The publication time limit was 2015 to 2020.Results: Adolescents who experienced an earthquake were found to demonstrate a high prevalence of post-traumatic stress disorder with the proportion in girls being higher than boys. Showing social support has a significant effect on PTSD after an earthquake. The earthquake-related factors that were the most strongly associated with probable PTSD were feeling scared of dying and exposure to an earthquake.Conclusion: Social support and the prevalence rates of PTSD should be observed in more detail. These results indicate that it is important to provide and strengthen the social support available to reduce the risk and severity of post-traumatic stress disorder after an earthquake among adolescents.